Characteristics of the levels of formation of the control action in younger schoolchildren - Tolipov R. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, we are talking about one of the relevant issues at the same time is the question of the formation of the teacher’s control skills as the most important component in the general context of personality formation.